2019
DOI: 10.1002/jcsm.12428
|View full text |Cite
|
Sign up to set email alerts
|

Muscle wasting and function after muscle activation and early protocol‐based physiotherapy: an explorative trial

Abstract: Background Early mobilization improves physical independency of critically ill patients at hospital discharge in a general intensive care unit (ICU)‐cohort. We aimed to investigate clinical and molecular benefits or detriments of early mobilization and muscle activating measures in a high‐risk ICU‐acquired weakness cohort. Methods Fifty patients with a SOFA score ≥9 within 72 h after ICU admission were randomized to muscle activating measures such as neuromuscular elect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
15

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 63 publications
(95 citation statements)
references
References 32 publications
(65 reference statements)
2
70
0
15
Order By: Relevance
“…The findings may also suggest that muscle size may not be the best predictor of outcomes, specifically ICU-AW. Muscle mass or size has previously been shown not to correlate with muscle strength [ 69 , 70 ], potentially demonstrating that atrophy may not be the primary culprit of ICU-AW. These data, interpreted with caution, may support that deteriorations in muscle quality and muscle power may partially explain development of ICU-AW.…”
Section: Discussionmentioning
confidence: 99%
“…The findings may also suggest that muscle size may not be the best predictor of outcomes, specifically ICU-AW. Muscle mass or size has previously been shown not to correlate with muscle strength [ 69 , 70 ], potentially demonstrating that atrophy may not be the primary culprit of ICU-AW. These data, interpreted with caution, may support that deteriorations in muscle quality and muscle power may partially explain development of ICU-AW.…”
Section: Discussionmentioning
confidence: 99%
“…74 Neuromuscular electrical stimulation has been shown to prevent muscle atrophy via induction of protein synthesis, although a clinical outcome benefit has not yet been unequivocally established. 75,76 A differing contractile response to neuromuscular electrical stimulation has been hypothesized as a reason for that lack of clinical effectiveness, and future research into different protocols, as well as the underlying mechanisms, behind the postulated differing contractile response is still warranted. Functional electrical stimulation combines neuromuscular electrical stimulation and in-bed cycling, thus coupling the muscle stimulation with the corresponding movements.…”
Section: Active Mobilization In Unconscious Patientsmentioning
confidence: 99%
“…The myocyte cross-sectional area of the intervention group was significantly higher (type I + 36%, type IIa + 49%, type IIb + 65%, p < 0.001 for all) compared to the control group (type I + 10%, type IIa + 13%, type IIb + 3%, p < 0.001 for all). This increase was accompanied by regulated gene expression for myosin heavy chains (fold change median [IQR]: MYH1 2.3 [1.1 -2.7], MYH2 0.7 [0.2 -1.8]; MYH4 5.1 [2.2 -15.3]) indicating that the muscle protein synthesis pathway was activated, probably due induced by muscle activation [16].…”
Section: Parameters Of Nmes and Local Effectsmentioning
confidence: 99%
“…Since a large proportion of critical patients cannot participate in any active mobilization, neuromuscular electrical stimulation (NMES) may be an alternative strategy for muscle training [13]. NMES has been used in protocols of early mobilization in ICU with the objective of reversing muscle weakness, preserving muscle mass and preventing atrophy, preserving function and reducing complications and disability [13] [14] [15] [16]. In addition, studies have shown that its application is safe and viable [17] [18] [19].…”
Section: Introductionmentioning
confidence: 99%